1996
DOI: 10.1111/j.1469-0691.1996.tb00196.x
|View full text |Cite
|
Sign up to set email alerts
|

IgG avidity in the serodiagnosis of acute Toxoplasma gondii infection: a multicenter study

Abstract: OBJECTIVE: To evaluate the validity of the IgG avidity test in the serodiagnosis of acute T. gondii infection; to verify the maturation of IgG avidity during the course of infection; to observe whether the kinetics of IgG maturation could be affected by antibiotic treatment. METHODS: Serial serum samples, collected in three Italian hospitals (Perugia, Treviso and Bologna), from untreated and antibiotic-treated patients with primary toxoplasmic infection, were assayed for IgG avidity, and IgM and IgA positivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
47
0
5

Year Published

1997
1997
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 13 publications
4
47
0
5
Order By: Relevance
“…The observation that T. gondii-specific IgG maturation is delayed in treated pregnant women compared to nontreated individuals was reported in one previous study, which found significantly delayed IgG maturation in treated individuals (25). Our finding that treatment may influence IgG maturation emphasizes the need for further studies to better clarify the avidity maturation process in pregnant women receiving therapy in comparison with nontreated individuals.…”
Section: Discussionmentioning
confidence: 47%
“…The observation that T. gondii-specific IgG maturation is delayed in treated pregnant women compared to nontreated individuals was reported in one previous study, which found significantly delayed IgG maturation in treated individuals (25). Our finding that treatment may influence IgG maturation emphasizes the need for further studies to better clarify the avidity maturation process in pregnant women receiving therapy in comparison with nontreated individuals.…”
Section: Discussionmentioning
confidence: 47%
“…Among these parameters, the sex of the person, pregnancy, immunodepression, and the type of treatment given have been cited (6,19,22). Starting treatment early in pregnant women could affect the increase in avidity (22). This hypothesis supported by some authors (6,19) has not, however, been confirmed by large-scale studies.…”
mentioning
confidence: 49%
“…Different parameters can modify the increase in the AI during the course of seroconversion. Among these parameters, the sex of the person, pregnancy, immunodepression, and the type of treatment given have been cited (6,19,22). Starting treatment early in pregnant women could affect the increase in avidity (22).…”
mentioning
confidence: 99%
“…In addition, the presence of IgM negativity resulting from inappropriate timing of blood sampling or the loss of EBNA antibodies owing to a suppressed immune system can obscure the identifi cation of primary infections or can lead to misdiagnosis. In such cases, it is suggested that the study of IgG avidity is critical to interpreting serological results correctly (9)(10)(11)(12). In general, the kinetics of affi nity maturation occurs in a couple of weeks; however, in some cases this maturation process may arise within three months after the onset of symptoms.…”
Section: Discussionmentioning
confidence: 99%